(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Authors give new data on the parasitoids of Cosmopterix pulchrimella Chambers (= C. parietariae Hering) (Lepidoptera Cosmopterigidae), listing Cirrospilus diallus Walker, C. pictus (Nees), Colastes flavitarsis Thomson, Ratzeburgiola sp. aff. incompleta Boucek and Diadegma exareolator Aubert. C. diallus has also been obtained from Euleia heraclei (L.) (Diptera Tephritidae) living on Smyrnium olusatrum L.. Another Eulophid wasp was emerged from C. pulchrimella, identified as belonging to gen. Cleolophus Mercet, seems to be different from the sole species known in Italy for this genus. C. pictus, particularly, and C. diallus were already known as antagonists of Phyllocnistis citrella Stainton, key-pest of the citrus grove. Thus, it is confirmed the role of C. pulchrimella as alternative host for them and its function of natural reservoir of parasitoids.